Lives Per Gallon: The True Cost of Our Oil Addiction - Tamminen Terry (Island Press, 2009)
The infamous "pain at the pump" runs much deeper than our wallets, argues Terry Tamminen, former Secretary of the California Environmental Protection Agency and current Special Assistant to California Governor Arnold Schwarzenegger. Petroleum may power our cars and heat our homes, but it also contributes to birth defects and disorders like asthma and emphysema, not to mention cancer. In Lives Per Gallon, Tamminen takes a hard look at these and other health, environmental, and national security costs hidden in every barrel of oil.